2011
DOI: 10.1371/journal.pone.0022307
|View full text |Cite
|
Sign up to set email alerts
|

Development and Disease: How Susceptibility to an Emerging Pathogen Changes through Anuran Development

Abstract: Ranaviruses have caused die-offs of amphibians across the globe. In North America, these pathogens cause more amphibian mortality events than any other pathogen. Field observations suggest that ranavirus epizootics in amphibian communities are common during metamorphosis, presumably due to changes in immune function. However, few controlled studies have compared the relative susceptibility of amphibians to ranaviruses across life stages. Our objectives were to measure differences in mortality and infection pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 56 publications
1
68
0
Order By: Relevance
“…If all stages were equally susceptible, mortality in wood frog populations would occur in spring, which was not observed. Haislip et al ( 2011 ) also found that susceptibility to ranavirus differed among amphibian developmental stages, but metamorphosis was not always the most susceptible stage. Thus, the occurrence of metamorphosis is not a universal explanation for timing of ranavirus outbreaks in amphibian communities.…”
Section: Susceptibility Throughout Developmentmentioning
confidence: 89%
See 3 more Smart Citations
“…If all stages were equally susceptible, mortality in wood frog populations would occur in spring, which was not observed. Haislip et al ( 2011 ) also found that susceptibility to ranavirus differed among amphibian developmental stages, but metamorphosis was not always the most susceptible stage. Thus, the occurrence of metamorphosis is not a universal explanation for timing of ranavirus outbreaks in amphibian communities.…”
Section: Susceptibility Throughout Developmentmentioning
confidence: 89%
“…There are a growing number of experimental studies investigating the relative susceptibility of amphibian species to ranavirus infection and disease (Cullen et al 1995 ;Cullen and Owens 2002 ;Schock et al 2008 ;Hoverman et al 2010Hoverman et al , 2011Haislip et al 2011 ). Until the recent studies by Brenes et al ( 2014a , b ), comparative studies involving reptiles were generally lacking, and those involving fi sh are largely restricted to EHNV (Becker et al 2013 ;Langdon 1989 ; but see Brenes et al 2014b ).…”
Section: Susceptibility To Ranaviruses Among Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Earl and Gray ( 2014 ) demonstrated that ranavirus-associated mortality of larvae or metamorphs was suffi cient to cause population declines in highly susceptible species. Researchers have demonstrated a strong correlation between infection prevalence and mortality in laboratory experiments with Frog Virus 3 (FV3)-like ranaviruses (see Haislip et al 2011 ;Hoverman et al 2011 ;Brenes et al 2014a ); thus, high infection prevalence during fi eld surveillance may be an indicator of an impending die-off .…”
Section: Field and Clinical Findingsmentioning
confidence: 99%